Planning For Wind Energy: Evaluating Municipal Wind Energy Land Use Planning Frameworks in Southwestern Ontario with a Focus on Developing Wind Energy Planning Policies for the City of Stratford - Longston, Kristopher, J. (University of Waterloo, 2006)
Wind energy provides an environmentally friendly and renewable source of electricity, that can help meet Canada's Kyoto commitments, help safeguard against future blackouts, reduce air pollution and create economic opportunities in the form of manufacturing jobs and land leases for farmers. From a land use planning perspective, however, wind turbines create challenges that municipalities and planners have to deal with more frequently. Ontario in particular lags behind countries such as Ireland and Australia in terms of providing a clear, equitable and comprehensive land use planning framework to deal with wind energy.
What is lacking in particular is a clear understanding of how Ontario municipalities are dealing with the issue of wind energy developments, whether the policies that are being developed adhere to good planning principles, what are the land use planning issues that are impacting wind energy development in Ontario and what are some recommendations that could be made to improve wind energy policies. A secondary goal of this thesis was to identify common elements of good wind energy planning frameworks that could be used to develop wind energy planning policies in the City of Stratford, which currently does not have any policies or a wind energy land use planning framework and is also where the author is employed as the City Planner.
To address this lack of information, this report focuses on the current state of wind energy planning policy development in southwestern Ontario and in particular; the types of wind energy planning frameworks have been developed in the world, the elements of "good" planning principles and frameworks and whether or not they are found in these frameworks, whether there are components of these policies that would be appropriate for wider adoption in Ontario and finally, what types of framework should the City of Stratford develop for wind energy?
To address these questions, a literature review was conducted on wind energy land use planning issues and examples of international wind energy planning guidelines were reviewed. Additionally, five southwestern Ontario municipalities with wind energy policies were selected as case studies and Planners and other wind energy stakeholders were interviewed.
This study found that the main issues and barriers surrounding wind energy planning policy development in Ontario are visual impact, lack of education and a lack of a municipal planning framework. It was also determined that, the public reaction to wind energy proposals in Southwestern Ontario has been mostly positive and the conflicts that have arisen have been in instances where wind turbines are proposed in the vicinity of recreational properties. In terms of a wind energy planning framework, southwestern Ontario municipalities have for the most part opted for General Official Plan policies supporting wind energy development in principle and directing its development to certain land use designations subject to a zoning by-law amendment. The planning frameworks in the case studies for the most part conform to good planning principles identified, however, there was a large variation between the municipalities in terms of the level of detail within the planning framework. Finally, it was determined that the City of Stratford Official Plan and Zoning By-law are inadequate in terms of policy and regulations for wind energy.
This study recommends that the Ontario Provincial Government should follow up on the Wind Energy Information Sheet and the recent Provincial Policy Statement with a comprehensive land use-planning framework for wind energy developments that should borrow on existing international guidelines that have been developed. This study also recommends that the City of Stratford should update its Official Plan to include policies that address wind energy generation, should initiate a study to determine if there are any areas within the City that are considered to be natural heritage views or areas that should be protected from the visual impacts of wind energy production, should investigate permitting wind energy facilities in certain industrial areas of the City, subject to a zoning by-law amendment and should work with the County of Perth to develop a common set of zoning by-law regulations for wind energy developments.
Keywords: Planning; Planning; Wind Energy; Policy Framework